Characterization of Two Novel AmpC Beta-Lactamases from the Emerging Opportunistic Pathogen, Cedecea neteri - Stephen M. Sharkady; Brandon Bailey; Dorothea K. Thompson (MDPI AG, 2023)
The genus Cedecea (family Enterobacteriaceae) causes a wide spectrum of acute infections in immunocompromised hosts, from pneumonia and bacteremia to oral ulcers and dialysis-related peritonitis. While Cedecea infections are reported infrequently in the literature, documented clinical cases of this emerging opportunistic human pathogen have occurred worldwide. Cedecea neteri has clinical significance and exhibits antimicrobial drug resistance. However, little is known about the molecular basis underlying the resistance phenotypes in C. neteri. We previously hypothesized that the open-reading frame cnt10470 in the C. neteri SSMD04 genome encodes a chromosomal Ambler class C (AmpC) β-lactamase based on sequence homology. In this study, recombinant polyhistidine-tagged proteins were created by cloning the putative ampC genes from SSMD04 and C. neteri ATCC 33855 (a clinical isolate) into the pET-6xHN expression vector, overexpressing the proteins, and then purifying the recombinant AmpCs (rAmpCs) using immobilized metal affinity chromatography (Ni-NTA). The in vitro enzymatic analysis of the purified rAmpCs was performed to determine the Km and kcat for various β-lactam substrates. The rAmpCs are functional class C β-lactamases when assayed using the chromogenic β-lactamase substrate, nitrocefin. The presence of functional AmpCs in both C. neteri strains underscores the necessity of performing antibiotic susceptibility testing in the management of C. neteri infections.